HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN LANSIA DALAM MENJALANI PENGOBATAN HIPERTENSI DI PUSKESMAS GEMARANG MADIUN - Hariyadi, Hariyadi (Journal Nursing Care and Biomolecular, 2019)
Introduction: Until now, hypertension is still a major disease in Indonesia. Hypertension is a condition that is often found in primary health care. This hypertension is a health problem with a high prevalence of 25.8%, the Indonesian population suffers from hypertension. Methods: The type of research used is descriptive analytical with a correlational design that examines relationships between variables. By used a cross sectional approach. The sample size in this study according to Slovin could be determined by a formula based on the population in getting 80 samples. The sampling technique used in this study is Simple Random Sampling. The independent variable in this study was  family support. While the dependent variable in this study is the obedience of elderly people with hypertension in undergoing treatment for hypertension. The statistical test used is the Pearson Product Moment correlation test with ? = 0.05. Results and Analysis: Family support for elderly people with hypertension in the Gemarang Community Health Center, Madiun Regency obtained an average of 76.86, a median of family support of 79.05. Compliance with the elderly at the Gemarang Health Center in Madiun Regency obtained an average score of 89.76. There is a relationship between family support and adherence of elderly patients in undergoing hypertension treatment in Madiun District Health Center with p-value = (0,000) <? (0.05) and r value = 0.623 which means the two variables have a strong relationship. Discuss: There is a relationship between family support and adherence of elderly patients in undergoing hypertension treatment in Madiun District Health Center